THE EFFECT OF DUST EXPOSURE ON LUNG FUNCTION IN WORKERS IN PT CEMENT PUGER JAYA RAYA SENTOSA JEMBER - Ni Made Ayu Wulandari (Aloha International Journal of Health Advancement (AIJHA), 2020)
The purpose of this study was to influence dust exposure on lung function in workers at PT Cement Puger Jaya Raya Sentosa Jember. This research method was quantitative while based on time, including cross sectional. The number of samples in this study amounted to 40 samples, which were taken by proportional random sampling. The data obtained were further analyzed using the Spearman Rho test to test the effect of significance (α = 0.05). The results show that the pvalue